FROM FIT TO ENGAGEMENT: THE MEDIATING ROLE OF ORGANIZATIONAL CLIMATE IN AN INDONESIAN MANUFACTURING CONTEXT - Angella, Christine; Lianto, Lianto (Universitas Riau Kepulauan, 2025)
This study examines how person–organization fit (P–O Fit) shapes employee engagement by considering the mediating role of organizational climate within a regional manufacturing setting in Indonesia. Drawing on the Attraction–Selection–Attrition framework, Social Information Processing theory, and the Job Demands–Resources model, the research positions value congruence and shared workplace perceptions as central psychological mechanisms influencing employee motivation. Using a census-based sample of 65 employees from a mineral-water production company in West Kalimantan, the study employed WarpPLS 8.0 to evaluate both the measurement and structural models. The findings indicate that P–O Fit enhances employees’ perceptions of organizational climate and directly contributes to higher engagement, while organizational climate itself emerges as a strong predictor of engagement and partially mediates the link between P–O Fit and engagement. These results highlight the importance of alignment and climate-building practices in manufacturing environments, particularly in resource-constrained and regionally based organizations. The study contributes to the growing body of literature on engagement in emerging contexts and emphasizes that psychological and relational factors remain critical drivers of motivation even in highly structured industrial settings.